Adjunct Faculty Development: A Kenyan Perspective. Issue 1 (2nd January 2020) - Wanjohi, Lucy
Abstract: Much development has happened in the education sector in African countries. In Kenya, there has been a proliferation of institutions of higher learning. Severe cuts in government funding for public higher education have resulted in the privatization of higher education and the need for adjunct faculty as a way to cut costs. Research suggests that although there is a rise in reliance on adjunct faculty in many institutions of higher learning around the world, these faculty are not always adequately prepared for the challenges they meet in the classroom. This article explores the need for full-time as well as adjunct faculty development in institutions of higher learning in Kenya. It looks at ways in which adjunct faculty can be specifically offered professional development and how they can be integrated into the life of the institutions in which they teach. Finally, it proposes possible implications for carrying out adjunct faculty development.